DEVELOPMENT OF A TEACHING MODULE FOR READING FOLKLORE TEXTS BASED ON FLIP PDF DIGITAL POCKETBOOK - Sabrina, Annisa; Nur Eriyani, Reni; Ansoriyah, Siti (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The implementation of the Merdeka Curriculum in Indonesian language learning requires a text-based approach that emphasizes the ability to analyze and create various text types according to their communicative functions and social contexts. Folklore texts, as learning material for 10th-grade high school students, encounter obstacles in the contemporary students' comprehension process due to their linguistic characteristics, which utilize classical Malay language, and complex narrative structures. The dominance of conventional learning methods and limited learning media result in low student motivation and learning outcomes in understanding folklore texts. This research aims to develop a teaching module for reading folklore texts, which is based on a Flip PDF digital pocketbook, for 10th-grade students and to identify its usability and feasibility in Indonesian language learning. The research method employed a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, conducted at MAN 11 Jakarta during the 2023-2025 period. Data collection involved a needs analysis questionnaire administered to 34 students, validation by three experts (instructional design, media, and material), and a limited trial involving 48 students and three Indonesian language teachers. The results showed expert validation achieved an average score of 4.1-4.8, categorized as good to very good, teacher responses reached an average of 4.57 (very good), and student responses reached an average of 4.00 (good). The product proved effective in increasing student participation by 97.1%, who favored digital technology-based learning media. This research successfully created an innovative and interactive teaching module for reading folklore texts that is responsive to digital learning needs. Further development is suggested to conduct experimental research to measure its learning effectiveness and expansion to different text genres.